Meigs Syndrome, Pseudo-meigs Syndrome, Or Pseudo-pseudo Meigs Syndrome? A Case Report - Azie Jumaatul Adawiyah Nabir; Chiew Yee Lau; Adilah W. Ab Rahim; Aliyyah Mohammad Khuzaini (Elsevier, 2024)
Pediatric Hematology Oncology Journal Volume 9, Issue 4, December 2024, Pages 289-293